Step by step guide to AV production ([Pasig, Metro Manila] Philippine Human Resource Development Center)
Presents the basics of producing effective audio-visual slide shows. The key elements emphasized for such production are organization, creativity, simplicity, clarity and legibility.
Keywords: Audio-visual materials; Technology; Mass communication